Pollen and spore records constrained by millennial prodelta evolution: a case study of the Huanghe (Yellow River) delta - Hu, Weifen; Liu, Shihao; Liu, Yan; Feng, Aiping; Feng, Wei; Wang, Xiuhang; Chen, Shenliang (Frontiers in Marine Science, 2024)
Pollen and spore records in prodeltaic sediments hold significant potential for reconstructing paleoecologic and paleoclimatic evolution. However, uncertainties in these reconstructions arise from millennial-scale prodelta evolution, which dominates stratigraphic development and consequently influences sedimentary processes and/or pollen provenance. Here we explore the intricate relationship between pollen/spore records and prodelta stratigraphic evolution, using established seismic stratigraphy and ten sediment cores (five new, five from literature) within both the proximal and distal (mud belt) parts of the Huanghe (Yellow River) prodelta. In the proximal region, dominant lobate stratigraphic development, accompanied by shifts in river mouth and depocenter, leads to variations in pollen assemblages and contents within individual cores and differences in vertical pollen distribution across core sites. Transport distance appears to be a key factor, with arboreal pollens, particularly saccate ones (e.g., Pinus), positively correlating with the distance from the river mouth in their percentages within a single delta lobe, while non-arboreal and non-saccate arboreal pollens show higher percentages within shorter transport distances, despite longer distances leading to decreased total pollen concentrations. Likely due to the total pollen concentration after extended long-distance transport, this pattern is not observable in the distal mud belt. Subsurface stratigraphy in this mud belt reveals a complex pollen provenance characterized by Artemisia-Ulmus-Chenopodiaceae-Pinus, with non-arboreal pollens in dominance. Therein, non-arboreal pollens are not consistent with deposition from long-distance transport, and Ulmus pollens are uncommon in the western Bohai Sea. Interestingly, surface sediments in the mud belt display a different assemblage, characterized by Pinus-Artemisia-Quercus, consistent with the nearby Luanhe River prodelta, suggesting recent pollen supply from nearby sources, possibly due to the recent abandonment of the mud belt. Additionally, an energetic longshore transport/erosional regime reduces pollen content at the mud-belt margins and create pollen sinks (with the highest concentration) in the mud patch (accumulation area) within the erosion-dominated region adjacent to the mud belt. Our findings confirm that stratigraphic evolution, alongside hydrodynamic conditions and pollen provenance, governs pollen assemblages in deltaic/prodeltaic sediments. They can provide insights for palynological and pollen-based paleoclimatic and paleoecologic studies in other deltas.